Mesoporous Bi2S3/Bi2O3 Heterostructure-Based Sensors for Sub-ppm NO2 Detection at Room Temperature - Wei Liu; Jiashuo Chen; Ding Gu; Shupeng Sun; Xinlei Li; Xiaogan Li (Sensors, 2025)
Novel Bi2S3/Bi2O3 hybrid materials with unique mesoporous structures were successfully synthesized via a facile in situ elevated-temperature thermal oxidation method using the Bi2S3 as a precursor in air. The as-prepared Bi2S3/Bi2O3 heterostructure-based sensor exhibits an excellent performance for detecting sub-ppm concentrations of NO2 at room temperature (RT). In the presence of 8 ppm NO2, the sensor registers a response of approximately 7.85, reflecting a 3.5-fold increase compared to the pristine Bi2S3-based sensor. The response time is 71 s, while the recovery time is 238 s, which are reduced by 32.4% and 24.2%, respectively, compared to the pristine Bi2S3-based sensor. The Bi2S3/Bi2O3 heterostructure-based sensor achieves an impressively low detection limit of 0.1 ppm for NO2, and the sensor has been demonstrated to possess superior signal repeatability, gas selectivity, and long-term stability. The optimal preparation conditions of the hybrid materials were explored, and the formation of mesoporous structure was analyzed. The obviously improved gas sensitivity of the Bi2S3/Bi2O3 heterostructure-based sensor can be assigned to the combined influence of electronic sensitization and its distinctive morphological structure. The potential gas-sensitive mechanisms were revealed by employing density functional theory (DFT). It was found that the formation of heterostructures could enhance the adsorption energies and increase the amount of electron transfer between NO2 molecules and the hybrid materials. Furthermore, the electron redistribution driven by orbital hybridization between O and Bi atoms improves the capacity of NO2 molecules to capture additional electrons from the Bi2S3/Bi2O3 heterostructures. The content of this work supplies an innovative design strategy for constructing NO2 sensor with high performance and low energy consumption at RT.